Short leader sequences may be transferred from small RNAs to pre-mature mRNAs by trans-splicing in Euglena. - Tessier, L H (1991)
Very closely related short sequences are present at the 5' end of cytoplasmic mRNAs in Euglena as evidenced by comparison of cDNA sequences and hybrid-arrested translation experiments. By cloning Euglena gracilis nuclear DNA and isolating the rbcS gene (encoding the small subunit of ribulose-1,5-bisphosphate carboxylase/oxygenase), we have shown that the short leader sequence does not flank the nuclear gene sequence. The leader sequences were found to constitute the 5' extremities of a family of small RNAs. Sequencing six members of this family revealed a striking similarity to vertebrate U snRNAs. We propose that a trans-splicing mechanism transfers the spliced leader (SL) sequence from these small RNAs (SL RNAs) to pre-mature mRNAs. Transfer of leader sequences to mRNAs by trans-splicing has been shown only in trypanosomes where cis-splicing is unknown, and in nematodes where not more than 10% of the mRNAs have leader sequences. Our results strongly suggest that Euglena is a unique organism in which both a widespread trans-splicing and a cis-splicing mechanism co-exist.